WHAT TACTICAL DEFENSIVE BEHAVIORS WOULD HELP BRAZIL STOP GERMANY IN THE 7 TO 1? - Silva,Bruno Santos da (2022)
ABSTRACT The purpose of this research was to verify which tactical behaviors can predict defensive efficiency among elite football players. The sample was composed of 533 defensive sequences from national teams that were semifinalists in the FIFA World Cup 2014. An ad-hoc instrument was built with the variables: “ball recovery zone”, “defensive pressure”, “removing depth”, “defensive time spent”, “number of occupied corridors”, “number of fouls committed”, and “number of times fouled”. The tactical sequences were analyzed using Match Vision Studio Premium software. Multinomial logistic regression was applied to predict the chances of success and failure of collective defensive actions (P < 0.05). Recovering the ball in the defensive zone of the field had a 19-times better chance of goal completion compared to recovering the ball in the middle offensive zone (OR = 19.39; P < 0.01). On the other hand, removing defensive depth resulted in a decrease of 71% in the chances of completing a goal (OR = 0.29; P < 0.01). Moreover, every foul committed increased the chances of failure in the defensive phase (OR = 5.39; P < 0.01). Teams that recovered the ball far from their own goals and coordinated their last defensive line to leave attackers in an offside position had success in getting the ball back. Level of Evidence IV; Case series.